1985
DOI: 10.1099/0022-1317-66-4-757
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Response to Murine Cytomegalovirus. II. In vitro Requirements for Generation of Cytotoxic T Cells

Abstract: SUMMARYA cytotoxic response to murine cytomegalovirus (MCMV) was obtained by the culture of lymph node cells from mice inoculated with MCMV into both hind footpads 7 days previously. The cytotoxicity was mediated by Thy1.2 +, Lyt2 +, H-2-restricted effector cells and was virus-specific. Investigation of the in vitro conditions established that T cell proliferation was necessary for optimal generation of cytotoxicity, that proliferation was dependent upon Thyl.2 +, Lyt2 + cell populations and that supernatants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The detection of Tc cell precursors at 3 days post infection in draining lymph nodes is not unique to ectromelia infected mice and has been reported previously for mice infected with herpes simplex virus [ 16], and for cytomegalovirus [ 17]. A potential role for these cells in controlling virus infection must be considered.…”
Section: Discussionmentioning
confidence: 82%
“…The detection of Tc cell precursors at 3 days post infection in draining lymph nodes is not unique to ectromelia infected mice and has been reported previously for mice infected with herpes simplex virus [ 16], and for cytomegalovirus [ 17]. A potential role for these cells in controlling virus infection must be considered.…”
Section: Discussionmentioning
confidence: 82%
“…These high levels of virus appear to result in the generation of suppressive macrophages, which may magnify the effects of the difference in sensitivity of individual cells by blocking the development of effective T cell responses. Sinickas et al (1985) demonstrated that MCMV-specific cytotoxicity was expressed by BALB/c lymph node cells primed in vivo, only if they were cultured for 2 to 4 days prior to assay. This may be required for suppressive macrophages to die out.…”
Section: Discussionmentioning
confidence: 99%
“…inoculation of salivary gland MCMV, and harvest of draining popliteal LN followed by culture of single-cell suspensions. This and the accompanying paper (Sinickas et al, 1985) report the detailed characterization of the individual steps of the experimental protocol in order to study the kinetics, specificity and other relevant parameters of the cytotoxic response. As with HSV, the expression of cytotoxic potential against MCMV-infected MEF target cells was dependent upon a further period of time in vitro after the LN cells were removed from the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Viral doses of 102.6 or 10 `*.6 p.f.u. were then used in further experiments using this protocol as described in this and the accompanying paper (Sinickas et al, 1985).…”
Section: Kinetics Of Anti-mcmv Cytotoxic Activity With Different Viramentioning
confidence: 99%